A new financial stress index for Ukraine - Vladyslav Filatov (Graduate Institute of International and Development Studies, 2020)
This study improves on the methodology for calculating the financial stress index (FSI) for Ukraine by introducing time-varying correlation into the aggregation of 5 sub-indices (representing the banking sector, households, the corporate sector, government securities, and the foreign exchange (FX) market). The index consists of 20 indicators selected from an initial list of 47 potential candidates. To check the performance of the indicators, sub-indices, and index, we use area under the receiver operating characteristic curve (AUROC) and logit tests. Each sub-index is assigned a weight that reflects the impact of each market on the financial system. This new FSI peaks during periods of crisis that are in line with the consensus of financial experts and performs better than the previous FSI, which makes it more attractive for policy decisions. In particular, the new FSI can be used as a monitoring tool for the macroprudential policy of the National Bank of Ukraine.
Keywords: E44; G01; G18; 330; financial stability; financial stress index; indicator performance